2018
DOI: 10.4314/njt.v37i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of the Vertical Total Electron Content (VTEC) of the ionosphere at the GNSS cor station (SEERL) UNIBEN and three other cors stations in Nigeria

Abstract: The complex environment of the Sun-Earth, which resulted in the spatial and temporal variations of the ionosphere leads to different kinds of effects on human technologies. Man's continuous increasing utilization of space technologies in addressing it's immediate and future needs demand quality research of the space environments, to understand the physics of the interaction of the environment with systems (both space and earth bound), and to develop methods of mitigating the environmental effects. This is one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In addition, to calculate the statistical parameters, the length of the period was selected as about 55 days in order to minimize effects due to seasonal variations. (Richard, 2001;Liu JY et al, 2004;Cai CS, 2007;Liu LB et al, 2009;Liu LB and Chen YD, 2009;Liu LB and Wan WX, 2020;Olwendo et al, 2012;Elemo et al, 2018). The upper and lower bounds of the mentioned range can be calculated using the following Equations (1)−(4): , k and p are the 30-day TEC moving median value, TEC inter-quartile range, TEC upper bound, TEC lower bound, TEC observed value, differential of TEC, the threshold of the anomaly, and the percentage of TEC change from the undisturbed states, respectively.…”
Section: Tec Anomaliesmentioning
confidence: 99%
“…In addition, to calculate the statistical parameters, the length of the period was selected as about 55 days in order to minimize effects due to seasonal variations. (Richard, 2001;Liu JY et al, 2004;Cai CS, 2007;Liu LB et al, 2009;Liu LB and Chen YD, 2009;Liu LB and Wan WX, 2020;Olwendo et al, 2012;Elemo et al, 2018). The upper and lower bounds of the mentioned range can be calculated using the following Equations (1)−(4): , k and p are the 30-day TEC moving median value, TEC inter-quartile range, TEC upper bound, TEC lower bound, TEC observed value, differential of TEC, the threshold of the anomaly, and the percentage of TEC change from the undisturbed states, respectively.…”
Section: Tec Anomaliesmentioning
confidence: 99%
“…Based on Lloyd's seasonal classifications, the months can be categorised into three seasons corresponding to the June Solstice (May, June, July, and August), December Solstice (November, December, January, and February), and Equinox (September, October, March, and April) [13]. This preliminary modelling chooses Sq geomagnetic data during April 2011 (equinox) as described in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous other studies have indicated the presence of periodic signatures in the ionosphere at various locations on Earth (Xingliang et al, 2005;Cai, 2007;Afraimovich et al, 2008;Amiri-Simkooei and Asgari, 2011;Chauhan et al, 2011;Olwendo et al, 2012;Liu et al, 2014;Tariku, 2015;Elemo et al, 2018;Ogwala et al, 2019;Akinyemi et al, 2021). Note that the majority of characterization studies have been performed in low-latitude or high-latitude regions where geomagnetic activity dominates the physical processes.…”
mentioning
confidence: 99%